2018
DOI: 10.1039/c7fo01332a
|View full text |Cite
|
Sign up to set email alerts
|

Amaranth addition to enzymatically modified wheat flour improves dough functionality, bread immunoreactivity and quality

Abstract: Consumers with gluten-related disorders require gluten-free (GF) foods to avoid an immune response. Alternative to the use of non-gluten containing grains to prepare GF bread, the gluten reactivity has been greatly reduced using a proline specific cleavage enzyme, however, the gluten functionality was lost. The aim of this study was to evaluate the effect of adding an amaranth flour blend (AFB) to enzymatically modified wheat-flour proteins on dough functionality and to evaluate the immunoreactivity and accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…After 48 h of incubation, Walter et al [96] noted a reduction of 99% in the gluten content of wheat bran. Heredia-Sandoval et al [97] also obtained a reduction in gluten content of 98% in wheat flour at 8 h of incubation.…”
Section: Action Of Clavispora Lusitaniae Protease On Glutenmentioning
confidence: 87%
“…After 48 h of incubation, Walter et al [96] noted a reduction of 99% in the gluten content of wheat bran. Heredia-Sandoval et al [97] also obtained a reduction in gluten content of 98% in wheat flour at 8 h of incubation.…”
Section: Action Of Clavispora Lusitaniae Protease On Glutenmentioning
confidence: 87%
“…Although the subunits of higher m.w. (around 66 kDa) were represented by faded spots in Part A, the IgA from patients with CD clearly recognized them in Part B because they are the most immunogenic wheat proteins (8). The bread, cake, and tortilla with the highest gluten content and immune reactivity of IgA in patients with CD were from a popular brand with several bakeries and cafeterias in different Mexican cities, in addition to not having any GF certification.…”
Section: Discussionmentioning
confidence: 99%
“…Sample extraction was followed as described for ELISA analysis by Ridascreen Gliadin R7001. Electrophoresis and immunodetection were carried out as previously described in the laboratory (8). Briefly, GF extracts were mixed (1:1, v/v) with × 5 extraction buffer (0.3 M Tris-HCl [pH 6.8], 0.35 M SDS, 50% [v/v] glycerol, 0.05% [w/v] bromophenol blue, 0.05% [w/v] βmercaptoethanol, and 1,200 µL of water), vortexed for 20 min, heated at 95 • C for 10 min, and centrifuged at 12,000 g for 10 min.…”
Section: Sds-gel Electrophoresis Electro-blotting and Immuno-detectionmentioning
confidence: 99%
“…Heredia-Sandoval et al showed that addition of Amaranth flour to enzymatically pre-digested wheat was found to render it acceptable with good viscoelastic properties and at the same time less immune-reactive. The enzyme used in this study was the glutenase AN- PEP (68).…”
Section: Novel Therapies For Celiac Diseasementioning
confidence: 99%